The Influence of Human Resource Competence, Accounting Understanding, and the Application of Government Accounting Standards on the Quality of Local Government Financial Reports (An Empirical Study of OPDs in Palu City) - Gusnianti; Andi Mattulada Amir; Muhammad Ilham Pakawaru (Journal GoodWill, 2025)
This study aims to examine and analyze the influence of human resource competencies, accounting understanding, and the application of government accounting standards on the quality of local government financial reports, both simultaneously and partially. This is an empirical study using quantitative research methods and primary data. The population in this study is the Regional Apparatus Organization in Palu City. The sampling technique used in this study is saturated sampling, with respondents comprising all financial managers in all OPDs in Palu City, totaling 82 respondents. The analysis techniques used in this study are classical assumption tests, multiple linear regression analysis, and hypothesis tests, specifically the simultaneous test (F) and partial test (t). The results of this study indicate that human resource competence, accounting understanding, and the application of government accounting standards have a significant simultaneous effect on the quality of local government financial reports. Human resource competence has a significant partial effect on the quality of local government financial reports. Accounting knowledge does not have a significant partial effect on the quality of local government financial reports, while the application of government accounting standards has a significant partial effect on the quality of local government financial reports.